if p,q,r denote vectore b x c, c x a,a x b respectively then show that

Asked by  | 20th Feb, 2009, 05:32: PM

Expert Answer:

A x (B xC ) = B (A.C) - C(A.B)

q x r = (c x a) x (a x b)

= a( (c x a) .b ) - b ( (c x a) .a )   (c x a will be perpendicular to a so (c x a) .a = 0)

=a( (c x a) .b )

now a x (q x r ) = a x a ( (c x a) .b ) = 0 since a x a = 0

similarly we can prove for others.

Answered by  | 20th Feb, 2009, 10:07: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.